Mathematical simulation of promising turbo-prop engines for diagnostics purposes - Якименко, В. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the problems of mathematical simulation of promising turbo-prop engines for diagnostic purposes by means of non-evident diagnostic model. Mathematical model of serviceable technical conditions of turbo-prop engine ТВЗ-117ВМА-СБМ is proposed